Commodification In Public Sphere; The Fight Of Ideology Through Social Media - Arina Rohmatul Hidayah; Moch. Mukhlison (Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
This paper wants to present a critical perspective in reading the discourse that has been played on social media in the last few days. With literature review method, the KPK Taliban is a form of discourse in which ideological values which are basically the principle of a person or group in determining the direction and purpose of how to proceed, are modified in such a way as to be sold or made into public commodities for political interests. The use of the term Taliban which is associated with hardline of Islam, wants to form an Islamic government in accordance with Islamic laws, is considered have a high 'selling power' so that it can be used to reduce the image of KPK as a law enforcement agency. Like a word, every journalist will try to make interesting headline to get a high view of readers. This term can seem to describe that there has been an internal radicalization in KPK that has created a system of eradicating selective corruption based on the ideology of investigator. From this point of view, social media can be said to be an easy facilitator to explore discourses of this kind. Due to the absence of a gate keeper or news editor, anyone who has an interest in them is free to release any statement even if it is not accompanied by valid data. Even rational and critical discussions such as the basic concept of public sphere are transformed into irrational